On the robustness of estimates of genetic correlation - ., Sarika; Wahi, S D; Rao, A R (The Indian Journal of Animal Sciences, 2011)
Genetic correlation is one ofthe important genetic parameters widely used by the breeders and geneticists in selection and improvement programs. Evidences are cited in the literature for the estimation of genetic correlation based on normality assumptions. This paper presents the estimates ofgenetic correlation under non-normality assumptions, from the variance covariance components under half-sib model. The estimates of genetic correlation, bias, standard error and mean square error estimates are reported in the study.